IMPACT OF THE EASTERN SPECIAL DEVELOPMENT ZONE ENVIRONMENT ON CHINESE FOREIGN DIRECT INVESTORS IN THAILAND - Muensriphum, Chidchai; Makmee, Pattrawadee; Wongupparaj, Peera (Asian Administration and Management Review, 2023)
The purpose of the study was to examine the influence of Thailand’s Eastern Special Development Zone (ESDZ) Environment factors on Chinese Foreign Direct Investors’ (FDIs) business performance. A well-structured questionnaire was developed to collect data from 200 respondents using the random sampling technique. Statistical Packages for the Social Sciences were used for data analysis to produce relevant parameters. We then applied the Analysis of Moment Structures to test the causal relationships as well as to examine the acquired data. The results revealed that there was a significant direct and positive influence of the ESDZ Environment-Business Cost, Competitive Hostility, Labour Availability, and ESDZ Environmental Dynamism on Chinese FDIs’ business performance in Thailand’s ESDZ. Furthermore, we included Intercultural Competence and Business Strategy as two important latent variables alongside ESDZ Environment to be empirically tested in this research study. The practical implications of the current results contribute greatly to FDIs’ strategic planning in the region, especially the Chinese FDIs since the ESDZ Environment helps to improve the Chinese FDIs’ business performance. The novelty rests in its notion that analyzing and anticipating the ESDZ Environment is a necessary complement to improving these Chinese FDIs’ corporate performance.